2017
DOI: 10.1186/s12885-017-3269-6
|View full text |Cite
|
Sign up to set email alerts
|

The treatment of primary mediastinal large B-cell lymphoma: a two decades monocentric experience with 98 patients

Abstract: BackgroundThe purpose of this study is to investigate the most suitable first-line approach and the best combination treatment for primary mediastinal large B-cell lymphoma (PMLBCL) as they have been matter of debate for at least two decades.MethodsOur single centre experience in the treatment of 98 de novo PMLBCL patients over the last 20 years is reviewed. All patients received MACOP-B chemotherapy. Thirty-seven received both rituximab and mediastinal radiotherapy; 30 were irradiated after chemotherapy, alth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 37 publications
1
3
0
1
Order By: Relevance
“…Part of the cohort also received external mediastinal RT and/or anti-CD20 immunotherapy, depending on our institutional era-specific guidelines. The addition of rituximab did not imply a clear advantage as previously reported [ 27 ].…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Part of the cohort also received external mediastinal RT and/or anti-CD20 immunotherapy, depending on our institutional era-specific guidelines. The addition of rituximab did not imply a clear advantage as previously reported [ 27 ].…”
Section: Discussionsupporting
confidence: 70%
“…No formal sample size estimation and power calculation were made for this observational retrospective study as we consecutively enrolled all PMBCL patients who underwent MACOP-B as a first-line approach. Part of the cohort was the same used in our previous report which had the aim to assess the difference in the first-line approach (i.e., chemotherapy, radiotherapy, rituximab, or their combinations) [ 27 ]. The objective response rate (ORR) was calculated as the sum of partial and complete response rates.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research recorded a complete response rate of 62.2% for MCOP-B as the first-line treatment. 20 Dose-dense RCHOP-ICE resulted in 5-year PFS and OS rates of 93% and 98%, respectively. 21 Studies also reported the outcomes of R-CHOP-21 and DA-EPOCH-R-28 in PMBCL and suggested that R-CHOP-21 may be an alternative treatment regimen.…”
Section: Discussionmentioning
confidence: 97%
“…A prospect of cure for PMBL patients depends on the successful initial therapy because prognosis in case of disease progression or relapse is extremely poor 20 22 . The most common approach is currently R-CHOP 4 , 5 , 7 9 , 23 , 24 ± RT or DAEPOCH-R 11 , 12 , 23 , 24 ; more intensive protocols 13 , 15 , 25 , 26 are rarely used. Here we report the long term results of intensive alternating immunochemotherapy protocol GMALL/B-ALL/NHL2002 with high-dose cytarbine and intermediate-dose methotrexate followed by consolidative radiotherapy in 124 PMBL patients.…”
Section: Discussionmentioning
confidence: 99%